2015
DOI: 10.1016/j.rmed.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

New developments in inhaler devices within pharmaceutical companies: A systematic review of the impact on clinical outcomes and patient preferences

Abstract: Future developments of inhaler devices should all require well-designed studies to demonstrate patient benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 42 publications
(44 reference statements)
0
26
0
Order By: Relevance
“…However, as the majority (40/44) of the studies included in the NMA were blinded, it is unlikely that these differences in inhaler type would be reflected in the results. Currently, while several studies have identified patient preferences between different inhaler types [53][54][55], there is limited evidence to demonstrate any differences in efficacy outcomes [56,57]. Further research is therefore required to inform optimal device design, improve compliance, reduce handling errors and, ultimately, improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the majority (40/44) of the studies included in the NMA were blinded, it is unlikely that these differences in inhaler type would be reflected in the results. Currently, while several studies have identified patient preferences between different inhaler types [53][54][55], there is limited evidence to demonstrate any differences in efficacy outcomes [56,57]. Further research is therefore required to inform optimal device design, improve compliance, reduce handling errors and, ultimately, improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is limited data exploring the impact of the new 'easier to use' devices on inhaler technique and clinical outcomes in real life. There is a trend towards few inhaler technique errors [88,89] and patient satisfaction favoring the newer devices, however, real-life, long-term data are not as yet available, and there is a call for well-designed studies in the future [90]. Until that time, training patients in all the steps required to use these newer inhaler devices is recommended [3].…”
mentioning
confidence: 99%
“…Both clinical efficacy and safety are essential properties when choosing inhaled medications (12). To reduce inhaler-related side effects, the ideal device should be easy to use, dose delivery should be independent of the inspiratory flow, and release of the aerosol should be slow and constant, favoring low oropharyngeal and high pulmonary deposition (13).…”
Section: Patient Safetymentioning
confidence: 99%
“…Several recent innovations have improved the efficacy and performance of inhaler devices. Along with technological progress, and ideally with a once-daily dosing, it is important for patients to acquire the ability to use devices properly (13). However, in an online survey applied to 245 COPD patients, fewer steps to operate the inhaler, confirmation that the dose had been taken correctly, and easy coordination of the breathing maneuver were considered more important to patients (37).…”
Section: Patient Preferencementioning
confidence: 99%